The Level of Psychological Security among Sample of Nizwa University students in the Sultanate of Oman - Al-Sawafi, Mohammed Nasser Said (Journal of Educational and Psychological Sciences, 2019)
This study aimed to find out the level of Psychological Security of Nizwa University students and to find out the differences in level of Psychological Security according to gender (males/ females), the sample included (238) males and females. In order to achieve the objectives of the study, the descriptive approach was used. The researcher used the Maslow scale for the sense of Psychological Security and interpolation by Dawani and Dirani (1983) in the Abdullah’s study (1996) after verifying its validity and stability. The study sample (238) students from Nizwa University in the Sultanate of Oman were randomly chosen. The findings of the study could be summarized as the following: there is a high level of Psychological Security with Nizwa University students according to the comprehensive Psychological Security scale with a median (2.24) feeling with Psychological Security compares to threat with average (2.29) and feeling love to hatred with average (2.25) feeling with loyalty to loneliness with average (2.19), there is a significant difference at the level of α=0.05 between males and females in favour of the males. In light of the results, a number of recommendations and proposals were submitted to enhance the level of psychological security among students of the University of Nizwa, and the general Omani and Arab universities.
Keywords: Psychological security; gender variable; university students; Nizwa university